Caregivers’ Experiences of Geriatric Emergency Management for Older Adults Receiving Long-Term Care in Turi, Sleman - Lhetare Murwa Embun Pratama; Yulia Wardani; Herlin Lidya (Jurnal Keperawatan Florence Nightingale, 2025)
The increasing life expectancy has led to a growing elderly population and a higher demand for long-term care, including in Turi District, Sleman. Older adults with high levels of dependency are at greater risk of experiencing geriatric emergencies such as falls, stroke, heart attacks, choking, and other acute conditions. These emergency situations often require a rapid response from family caregivers, who in reality frequently neglected.This study aimed to explore caregivers’ experiences in managing geriatric emergencies among older adults requiring long-term home care. A qualitative study with a phenomenological was conducted. Data were collected through in-depth interviews and focus group discussions involving 14 informants, consisting of six family caregivers of older adults receiving long-term care and eight elderly community health volunteers from Girikerto and Bangunkerto villages. Data were analyzed using thematic analysis with the assistance of NVivo 12 software. The findings revealed that emergency management by caregivers was often suboptimal and faced several barriers, including limited knowledge, fear of providing first aid, lack of training, inadequate equipment and facilities, and limited access to health services. Despite these challenges, caregivers demonstrated strong responsibility and commitment. The study recommends training and support to improve caregivers’ skills and confidence in delivering appropriate emergency care